Adhesive as well as preparation method and application thereof

Through the chemical crosslinking reaction of isocyanate with polymer polyols, small molecule alcohols and water, a polyurethane crosslinking structure is formed, which solves the problem of degradation of the bonding performance of existing adhesives under high temperature, oxygen and moisture, and achieves the Efficient bonding and aging resistance extend the service life of composite polymer coils.

CN119307215APending Publication Date: 2025-01-14BEIJING ORIENTAL YUHONG WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374121.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The adhesive performance of existing adhesives significantly decreased under the action of high temperature, oxygen and moisture, resulting in low peeling strength between the composite polymer coil and the base layer, which is prone to delamination, drumming or bonding failure, affecting service life. .

Method used

Chemical crosslinking reaction is carried out using isocyanate components and polymer polyols, small molecule alcohols and water to form a polyurethane crosslinking structure, and improve adhesion and aging resistance through foaming technology to form solvent-free and double-group portion of foam adhesive.

Benefits of technology

It significantly improves the adhesion and aging resistance between the composite polymer coil and the base layer, extends the service life, and solves the environmental pollution and health hazards of solvent-based adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068286160000131
    Figure BDA0005068286160000131
  • Figure BDA0005068286160000132
    Figure BDA0005068286160000132
  • Figure BDA0005068286160000141
    Figure BDA0005068286160000141
Patent Text Reader

Abstract

The invention provides an adhesive and a preparation method and application thereof, the adhesive comprises a component A and a component B, the component A is an isocyanate component, and the component B comprises polymer polyol, small molecule alcohol and water. The adhesive disclosed by the invention has good cohesiveness, aging resistance and the like, can be applied to bonding a composite high-molecular coiled material and a base layer, and can improve the bonding force of the composite high-molecular coiled material and the base layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bonding materials, and in particular to an adhesive and a preparation method and application thereof. Background Art

[0002] Thermoplastic polymer waterproofing membranes that are composited with fabrics (such as polyester non-woven fabrics) and other materials on the lower surface of waterproof materials are referred to as composite polymer membranes. During construction, a layer of adhesive needs to be applied to the surface of the base layer, and the composite polymer membrane is bonded to the surface of the base layer through the adhesive to achieve the bonding of the waterproof material to the surface of the base layer and play a waterproof role on the base layer.

[0003] However, in the related art, the adhesives used have poor properties such as adhesion and aging resistance, which results in low peel strength between the composite polymer coil and the base layer. Especially under long-term exposure to high temperature, oxygen, moisture, etc., the adhesion performance is significantly reduced, and problems such as delamination, bulging, and even adhesion failure are prone to occur, which seriously affects the service life of the composite polymer coil. Summary of the invention

[0004] The present invention provides an adhesive and a preparation method and application thereof, so as to at least solve the problem of poor adhesion and aging resistance of the adhesive in the prior art.

[0005] In one aspect of the present invention, an adhesive is provided, comprising a component A and a component B, wherein the component A is an isocyanate component, and the component B comprises a polymer polyol, a small molecule alcohol and water.

[0006] According to one embodiment of the present invention, the small molecule alcohol includes one or more diols with a carbon number of 2 to 9; preferably, the small molecule alcohol includes one or more diols with a carbon number of 4 to 8; and / or, in the B component, the mass percentage of the small molecule alcohol is 5% to 25%, preferably 5% to 15%; and / or, in the B component, the mass percentage of water is 0.1% to 1.5%.

[0007] According to one embodiment of the present invention, the polymer polyol includes polyether polyol and / or polyester polyol.

[0008] According to one embodiment of the present invention, the hydroxyl value of the polyether polyol is 164-168 mgKOH / g; and / or the polyether polyol includes a polyether polyol with a functionality of 3; and / or in the B component, the mass percentage of the polyether polyol is 15%-39%; and / or the hydroxyl value of the polyester polyol is 54-58 mgKOH / g; and / or the polyester polyol includes a polyester polyol with a functionality of 2; and / or in the B component, the mass percentage of the polyester polyol is 15%-39%.

[0009] According to one embodiment of the present invention, the B component also includes an auxiliary agent, and the auxiliary agent includes one or more of a pigment, a second plasticizer, an antioxidant, and a catalyst; preferably, the pigment includes red iron oxide and / or phthalocyanine green; preferably, the second plasticizer includes chlorinated paraffin; preferably, the catalyst includes an organic metal catalyst; preferably, in the B component, the mass percentage of the pigment is 0.2% to 5%; preferably, in the B component, the mass percentage of the second plasticizer is 5% to 25%; preferably, in the B component, the mass percentage of the antioxidant is 0.1% to 2%; preferably, in the B component, the mass percentage of the catalyst is 0.1% to 2%.

[0010] According to one embodiment of the present invention, the component A includes isocyanate modified by a silane coupling agent; and / or, the component A includes a first plasticizer.

[0011] According to one embodiment of the present invention, the silane coupling agent-modified isocyanate is obtained by modifying isocyanate with a silane coupling agent, wherein the isocyanate includes polymethylene polyphenyl isocyanate, and / or the silane coupling agent includes 3-mercaptopropyltriethoxysilane coupling agent (KH-580) and / or 3-mercaptopropyltrimethoxysilane coupling agent; and / or the second plasticizer includes chlorinated paraffin; and / or, in the A component, the mass percentage of the silane coupling agent-modified isocyanate is 50.1% to 80.9%; and / or, in the A component, the mass percentage of the first plasticizer is 5% to 25%.

[0012] According to one embodiment of the present invention, the adhesive is a foaming adhesive; and / or the volume ratio of the component A to the component B is 1:(1-1.2).

[0013] Another aspect of the present invention provides a method for preparing the above-mentioned adhesive, including a preparation process of the component A and a preparation process of the component B; the preparation process of the component A includes: modifying isocyanate with a silane coupling agent to obtain isocyanate modified by the silane coupling agent; mixing a first plasticizer and the isocyanate modified by the silane coupling agent to obtain the component A; the preparation process of the component B includes: uniformly mixing raw materials for forming the component B to obtain the component B; wherein the raw materials for forming the component B include polymer polyols, small molecule alcohols and water.

[0014] Another aspect of the present invention provides a use of the above adhesive in bonding a composite polymer coil and a base layer.

[0015] The adhesive provided by the present invention and its preparation method and application, the adhesive comprises two components, namely component A (isocyanate component) and component B (polyol component), the component B contains polymer polyol, small molecule alcohol and water, under such a composition system, component A and component B can undergo chemical crosslinking reaction, and play a bonding role based on the foaming process, which can effectively improve the adhesion and aging resistance (such as high temperature resistance, hydrolysis resistance) of the adhesive, so that after the composite polymer coil and the base layer are bonded with the adhesive, the adhesion (peel strength) between the composite polymer coil and the base layer can be significantly improved, and even after being subjected to high temperature, oxygen, moisture and the like for a long time, a relatively high adhesion can still be maintained (that is, a relatively high peel strength between the composite polymer coil and the base layer is maintained), thereby suppressing the problems of delamination, bulging, or even adhesion failure of the composite polymer coil bonded to the base layer, and improving the service life of the composite polymer coil.

[0016] In addition, the adhesive of the present invention also has good construction performance and has the advantages of safety and environmental protection, which is conducive to practical industrial application. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0018] In the related technology, the adhesives used have poor properties such as adhesion and aging resistance, which results in low peel strength between the composite polymer coil and the base layer. Especially under the influence of high temperature, oxygen, moisture, etc. for a long time, the bonding performance is significantly reduced, and problems such as delamination, bulging, and even bonding failure are prone to occur, which seriously affects the service life of the composite polymer coil.

[0019] For example, in the related art, the adhesives used in the construction of composite polymer coils are mainly solvent-based non-reactive adhesives. Such adhesives will volatilize a large amount of solvents when used, which will seriously pollute the environment and harm the health of construction operators. At the same time, since such products are non-reactive adhesives, they cannot form chemical cross-links and have poor adhesion, resulting in low peel strength between the composite polymer coil and the base layer, and poor long-term aging resistance. Under the influence of high temperature, oxygen, moisture, etc. for a long time, the adhesion performance is significantly reduced, and delamination, bulging, and even adhesion failure are prone to occur, which seriously affects the service life of the composite polymer coil.

[0020] After long-term research, the inventors of the present application discovered that forming a polyurethane cross-linked structure through a chemical cross-linking reaction of an isocyanate component and a polyol component (mainly cross-linking based on the reaction of an isocyanate group (NCO) and a hydroxyl group (OH)) and based on polyurethane foaming technology is a feasible direction for improving the adhesion and aging resistance of adhesives.

[0021] The application of traditional polyurethane foaming technology is mainly concentrated in the fields of foam blocks and foam filling, while in the field of composite polymer coil adhesives, polyurethane foaming technology using small molecule alcohols (such as dipropylene glycol (DPG)) as the main component is rarely used and reported. Taking DPG as an example, DPG usually plays the role of a chain extender in polyurethane materials, which makes the molecular chain of polyurethane prepolymer grow, thereby helping to improve the performance of the material. That is, DPG is an auxiliary additive, and its addition amount and effect are limited. Moreover, after chain extension, the molecular weight increases and the viscosity increases, which is not conducive to construction.

[0022] In view of this, an embodiment of the present invention provides an adhesive, including a component A and a component B, wherein the component A is an isocyanate component, and the component B includes a polymer polyol, a small molecule alcohol, and water.

[0023] According to the research of the inventor of the present application, component A is an isocyanate component and component B is a polyol component. When used, components A and B are mixed and coated on the surface of the base layer, and the composite polymer coil is attached to the surface of the base layer. Components A and B can be chemically cross-linked based on the reaction of NCO (mainly from the isocyanate in component A) and OH (mainly from the polymer polyols and small molecule alcohols in component B that contain OH) to form a polyurethane cross-linked structure, thereby ensuring a good bonding effect. In addition, foaming will occur during the reaction (the isocyanate in component A reacts with components such as water in component B to generate carbon dioxide gas to achieve foaming), which is beneficial for the adhesive layer formed by the chemical cross-linking reaction of components A and B to be more fully filled between the composite polymer coil and the base layer, thereby further ensuring the bonding effect. Among them, the introduction of small molecule alcohols into component B can significantly reduce the system viscosity of component B, and good construction performance can be maintained without the addition of solvents, thereby avoiding problems such as environmental pollution caused by solvent volatilization; at the same time, the polymer polyols and small molecule alcohols in component B can undergo cross-linking reaction with the isocyanate in component A (isocyanate component), which is beneficial to the formation of a polyurethane cross-linking structure, thereby improving the bonding effect and aging resistance effect.

[0024] Therefore, the adhesive of the embodiment of the present invention is a solvent-free, two-component foaming adhesive, which can bond the composite polymer coil and the base layer based on polyurethane foaming technology. The adhesive has good adhesion (bonding strength) and aging resistance, such as good heat resistance (high temperature resistance) and hydrolysis resistance. It can improve the adhesion (peel strength) between the composite polymer coil and the base layer, as well as the adhesion after aging under long-term high temperature, oxygen, moisture and other conditions (that is, even after being subjected to high temperature, oxygen, moisture and the like for a long time, it can still maintain a high adhesion (that is, maintain a high peel strength between the composite polymer coil and the base layer)), thereby inhibiting the composite polymer coil bonded to the base layer from delamination, bulging, or even bonding failure, thereby improving the service life of the composite polymer coil.

[0025] In the embodiment of the present invention, before the use of the adhesive, component A and component B are stored separately. When in use, component A and component B are mixed and then coated on the surface of the base layer. The polymer composite coil is then attached to the surface of the base layer. The adhesive coated between the base layer and the composite polymer coil is cured through curing and other processes to form an adhesive layer. Under the composition system of component A and component B, the bonding strength, physical and mechanical properties and aging resistance of the adhesive layer can be improved, thereby improving the bonding strength between the composite polymer coil and the base layer and its bonding strength after long-term aging.

[0026] In addition, the adhesive of the embodiment of the present invention can maintain good construction performance without using solvents, and can also solve the problems of flammability, explosion, strong odor, inability to perform chemical cross-linking, and environmental pollution that exist in solvent-based adhesives. Specifically, neither component A nor component B contains solvent, and when the adhesive is used, when component A and component B are mixed, no solvent needs to be added.

[0027] Generally, component A and component B are both in liquid state, and the volume ratio of component A to component B can be 1:(1-1.2), for example, 1:1; the density ratio of component A to component B can be about 1.1:1.

[0028] Specifically, the small molecule alcohol refers to a non-polymer alcohol, which may include alcohol compounds with 2 to 9 carbon atoms, such as 2, 3, 4, 5, 6, 7, 8 or 9. The small molecule alcohol may be a diol.

[0029] In some embodiments, the small molecule alcohol includes one or more diols with a carbon number of 2 to 9, and the carbon number is, for example, 2, 3, 4, 5, 6, 7, 8 or 9, preferably one or more diols with a carbon number of 4 to 8, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0030] Specifically, the small molecule polyol may include one or more of ethylene glycol (EG), 1,4-butanediol (BG), 1,2-octanediol (OD), and 1,9-nonanediol.

[0031] In some embodiments, the small molecule alcohol includes dipropylene glycol (DPG).

[0032] In some embodiments, in component B, the mass percentage of small molecule alcohol is 5% to 25%, for example, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25% or a range composed of any two of them, preferably 5% to 15%, which is beneficial to reduce the viscosity of component B and the adhesive after mixing component B and component A, further improve the construction performance of the adhesive, and avoid excessive consumption of NCO provided by component A, as well as incomplete curing caused by the consumption, which in turn affects the bonding effect. Therefore, by controlling the content of small molecule alcohol in component B within the above range, it is beneficial to further improve the construction performance of the adhesive, and further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0033] In some embodiments, the mass percentage of water in component B is 0.1% to 1.5%, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5% or a range composed of any two of them. By introducing an appropriate amount of water, the cross-linking reaction of components A and B and the foaming during the cross-linking reaction are facilitated, the foaming efficiency is improved, and the adhesion and aging resistance of the adhesive are further improved, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0034] Generally, polymer polyols may include polyether polyols and / or polyester polyols, which are compatible with the above-mentioned component A and small molecule alcohols and water in component B, further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0035] Among them, the polyether polyol may include a multifunctional polyether polyol, specifically a trifunctional polyether polyol, which is beneficial to foaming during the cross-linking reaction of component A and component B, further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0036] In some embodiments, the hydroxyl value of the polyether polyol can be 164 to 168 mgKOH / g, which has more suitable properties such as molecular weight, which is beneficial to the bulk strength of the bonding layer formed by component A and component B after the chemical cross-linking reaction, making it less likely to be destroyed, improving its aging resistance, and at the same time helping to improve its adhesion, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0037] In some specific embodiments, the polyether polyol may include one or more of polypropylene oxide polyol, polyethylene oxide and poly(propylene oxide-ethylene oxide) copolymer polyol. For example, the polyether polyol used includes polypropylene oxide polyol with brand MN-700 from Shandong Dexin Federal Chemical Co., Ltd.

[0038] In some embodiments, in component B, the mass percentage of polyether polyol is 15% to 39%, for example, 15%, 20%, 25%, 30%, 35%, 39% or a range composed of any two of them, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0039] In addition, the polyester polyol may include a multifunctional polyester polyol, specifically a difunctional polyester polyol, which is compatible with the above-mentioned component A and small molecule alcohols and water in component B, further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0040] In some embodiments, the hydroxyl value of the polyester polyol can be 54-58 mgKOH / g, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0041] In some embodiments, in component B, the mass percentage of polyester polyol is 15% to 39%, for example, 15%, 20%, 25%, 30%, 35%, 39% or a range composed of any two of them, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0042] In addition, component B may further include an auxiliary agent, which may include one or more of a pigment, a second plasticizer, an antioxidant, and a catalyst.

[0043] Among them, by introducing a catalyst (or gel catalyst (used to react components A and B and perform gel curing) into component B, in the application process of the adhesive, after components A and B are mixed and coated on the base layer, and the composite polymer coil is attached to the surface of the base layer, it is beneficial to regulate the cross-linking reaction rate of components A and B, improve the initial adhesion of the reaction system of components A and B, shorten the reaction time, improve the reaction efficiency, and further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0044] In some embodiments, the catalyst may include an organic metal catalyst, specifically an organic tin catalyst, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0045] In some embodiments, in component B, the mass percentage of the catalyst is 0.1% to 2%, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2% or a range composed of any two of them, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0046] In some embodiments, the second plasticizer may include chlorinated paraffin, which is beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0047] In some embodiments, in component B, the mass percentage of the second plasticizer is 5% to 25%, for example 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25% or a range composed of any two of them, which is beneficial to regulating the viscosity and other properties of component B, and is more conducive to the adaptation of component B and component A, so that the dosage ratio (volume ratio) of the two is closer to 1:1, which is convenient for on-site construction operations, and is also beneficial to further improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0048] In some embodiments, in component B, the weight percentage of the antioxidant is 0.1% to 2%, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2% or any two thereof.

[0049] In some embodiments, the pigment may include red iron oxide and / or phthalocyanine green.

[0050] In some embodiments, in component B, the mass percentage of the pigment is 0.2% to 5%, for example, 0.2%, 0.7%, 1%, 2%, 3%, 4%, 5% or any two thereof.

[0051] In addition, component A may include isocyanate modified by a silane coupling agent. The isocyanate modified by a silane coupling agent is obtained by modifying isocyanate by a silane coupling agent. The isocyanate is grafted and modified by a silane coupling agent so that the isocyanate group (NCO) in component A and the hydroxyl group (OH) in component B react to form a polyurethane-silane coupling agent structure, which is beneficial to further improve the physical and mechanical properties of the adhesive, improve the adhesion and aging resistance of the adhesive, and thus further improve the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0052] In some embodiments, the isocyanate includes polymethylene polyphenyl isocyanate, which is beneficial to further enhance the physical and mechanical properties of the adhesive, improve the adhesion and aging resistance of the adhesive, thereby further enhancing the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0053] Among them, the silane coupling agent may include a silane coupling agent containing active hydrogen on the functional group (that is, it contains a reactive group with active hydrogen, which can react with groups such as NCO in component A, which is beneficial to the chemical cross-linking reaction of component A and component B), which is beneficial to the grafting of the silane coupling agent to the isocyanate, modifying the isocyanate to obtain the silane coupling agent-modified isocyanate, and is beneficial to further improve the physical and mechanical properties of the adhesive, improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0054] In some embodiments, the silane coupling agent includes 3-mercaptopropyltriethoxysilane coupling agent (KH-580) and / or 3-mercaptopropyltrimethoxysilane coupling agent, which is beneficial to further improve the physical and mechanical properties of the adhesive, improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0055] In some embodiments, in component A, the mass percentage of isocyanate modified by silane coupling agent is 50.1% to 80.9%, which is beneficial to further improve the physical and mechanical properties of the adhesive, improve the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0056] In addition, component A may also include a first plasticizer, which is beneficial for regulating the viscosity and other properties of component A, and is more conducive to the adaptation of component A and component B, so that the usage ratio (volume ratio) of the two is closer to 1:1, which is convenient for on-site construction operations, and is also beneficial for further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0057] The first plasticizer in component A and the second plasticizer in component B may be the same or different.

[0058] In some embodiments, the second plasticizer includes chlorinated paraffin, which is more conducive to the compatibility of component A and component B, facilitates on-site construction operations, and is conducive to further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0059] In some embodiments, in component A, the mass percentage of the first plasticizer is 5% to 25%, for example 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25% or a range composed of any two of them, which is more conducive to the adaptation of component A and component B, convenient for on-site construction operations, and conducive to further improving the adhesion and aging resistance of the adhesive, thereby further improving the adhesion between the composite polymer coil and the base layer and its adhesion after long-term aging.

[0060] The embodiment of the present invention further provides a method for preparing the above-mentioned adhesive, including a preparation process of component A and a preparation process of component B.

[0061] The preparation process of component A includes: modifying isocyanate with a silane coupling agent to obtain isocyanate modified by the silane coupling agent; and mixing the first plasticizer and the isocyanate modified by the silane coupling agent to obtain component A.

[0062] Specifically, the process of modifying isocyanate with a silane coupling agent may include: reacting isocyanate and silane coupling agent at room temperature (25°C ± 5°C), and the reaction time may be 0.5h to 3h (e.g. 1h), to obtain isocyanate modified with silane coupling agent. The process of modifying isocyanate with a silane coupling agent (i.e. the process of reacting isocyanate and silane coupling agent) may be carried out under stirring.

[0063] In specific implementation, isocyanate and silane coupling agent can be added to the reaction kettle, stirring is started, and the preset reaction time is maintained; then the first plasticizer is added thereto, and stirring is continued (for example, stirring for 0.5h to 3h (for example, 1h)) to mix the system evenly, and then the material is discharged to obtain component A.

[0064] The preparation process of component B includes: uniformly mixing raw materials for forming component B to obtain component B; wherein the raw materials for forming component B include polymer polyols, small molecule alcohols and water.

[0065] In specific implementation, polyether polyol, polyester polyol, pigment, second plasticizer, antioxidant, small molecule alcohol, water and catalyst can be added to the reaction kettle in sequence, stirring and high-speed dispersion can be started, and the stirring time can be 0.5h to 3h (for example, 1h) to mix the system evenly, and then discharge the material to obtain component B.

[0066] In the embodiment of the present invention, during the preparation of component A and component B, a conventional reaction kettle with a stirring function in the art may be used, and no particular limitation is imposed on this.

[0067] In the embodiments of the present invention, the materials used, such as silane coupling agent, isocyanate, plasticizer, polyether polyol, polyester polyol, pigment, plasticizer, antioxidant, small molecule alcohol, catalyst, etc., can be obtained by conventional methods in the art, such as commercial purchase or self-made by conventional methods in the art. For example, the plasticizer (first plasticizer, second plasticizer) used can include 52# chlorinated paraffin; the isocyanate used can be polymethylene polyphenyl isocyanate, brand PM-200 (Wanhua Chemical Group Co., Ltd.); the polyether polyol used has a functionality of 3, a hydroxyl value of 164-168 mgKOH / g, and a brand name of MN-700 (Shandong Dexin Federal Chemical Co., Ltd.); the polyester polyol used has a functionality of 2, a hydroxyl value of 54-58 mgKOH / g, and a brand name of 5520 (Shanghai Huide Technology Co., Ltd.); the antioxidant model used is 1010 (BASF Polyurethane (China) Co., Ltd. (BASF)); the water used is purified water or distilled water; the composite polymer membrane is a composite polymer membrane model TPO-FS2-1.2 of Oriental Yuhong Waterproof Technology Co., Ltd.

[0068] The embodiment of the present invention also provides an application of the above adhesive in bonding a composite polymer coil and a base layer.

[0069] When the adhesive of the embodiment of the present invention is used, component A and component B are mixed, and then coated on the surface of the base layer, and then the composite polymer coil is attached (pasted) to the surface of the base layer, and then pressed to ensure that the composite polymer coil does not warp and is well attached; then curing is performed, specifically, curing can be performed under the conditions of a temperature of 23±2°C and a humidity of 50%±5%, so that component A and component B undergo a chemical cross-linking reaction to form an adhesive layer to bond the composite polymer coil and the base layer. Under the composition system of the above-mentioned component A and component B, the bonding strength, physical and mechanical properties, and aging resistance of the adhesive layer can be improved, thereby improving the bonding force between the composite polymer coil and the base layer and its bonding force after long-term aging.

[0070] In the embodiment of the present invention, the composite polymer roll material may be a conventional thermoplastic polymer waterproof roll material in the art, which includes, for example, a TPO waterproof roll material, and specifically may include fabrics (such as polyester non-woven fabrics) and the like.

[0071] In the embodiment of the present invention, the base layer may be a conventional base layer in the art, for example, a concrete base layer, such as a wall of a building.

[0072] In the embodiment of the present invention, the composition of component A and component B can be analyzed by conventional analysis means such as gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance analysis.

[0073] The present invention is further described below by way of specific examples. In the following examples and comparative examples, unless otherwise specified, the polymethylene polyphenyl isocyanate used is PM-200 (Wanhua Chemical Group Co., Ltd.); the isocyanate MDI-50 used was purchased from Wanhua Chemical Group Co., Ltd.; the polyether polyol (polypropylene oxide polyol) used was 3-functionality, hydroxyl value 166 mgKOH / g, brand MN-700 (Shandong Dexin Federal Chemical Co., Ltd.); the polyester polyol used was 2-functionality, hydroxyl value 56 mgKOH / g, brand 5520 (Shanghai Huide Technology Co., Ltd.); the antioxidant model used was 1010 (BASF); the water used was purified water or distilled water; the catalyst used was an organic tin catalyst purchased from Guangzhou Yourun Synthetic Materials Co., Ltd.

[0074] Example 1

[0075] 1. Preparation of adhesive

[0076] The adhesive provided in this embodiment 1 includes component A and component B, the volume ratio of component A to component B is 1:1, and the preparation processes of component A and component B are as follows.

[0077] Preparation process of component A: polymethylene polyphenyl isocyanate and silane coupling agent (KH-580) are put into the reaction kettle in turn, stirring is started, and maintained for 1 hour to obtain isocyanate modified by silane coupling agent; then the first plasticizer (52# chlorinated paraffin) is added thereto, stirring is continued for 1 hour, and then the material is discharged to obtain component A.

[0078] Preparation process of component B: polyether polyol, polyester polyol, small molecule alcohol, pigment (phthalocyanine green), second plasticizer (52# chlorinated paraffin), antioxidant, water and catalyst are put into the reaction kettle in sequence, stirring and high-speed dispersion are started, high-speed stirring is carried out for 1 hour, and then the material is discharged to obtain component B.

[0079] 2. Application and performance testing of adhesives

[0080] In the following application and testing process, the composite polymer membrane used is from Oriental Yuhong Waterproof Technology Co., Ltd., model TPO-FS2-1.2.

[0081] (1) Preparation of peeling specimens: Component A and component B were mixed in a volume ratio of 1:1 (without adding solvent), stirred evenly, and then evenly applied on a concrete test block (base layer). After keeping at room temperature for 10 to 15 minutes, the composite polymer roll was pasted on the concrete test block and pressed with a 1 kg pressing piece to ensure that the roll did not warp and was well fitted; then, the roll was cured at 23°C and a humidity of 50% for 7 days to obtain a peeling specimen.

[0082] (2) Aging test

[0083] (2-1) The peel strength between the composite polymer membrane and the concrete specimen in the peeling specimen was directly tested without aging treatment. The test results (peel strength before aging) are shown in Table 1.

[0084] (2-2) The peeling specimen was placed in an oven and aged at 80°C for 168 h (i.e., kept in an oven at 80°C for 168 h). The peeling strength between the composite polymer membrane in the peeling specimen and the concrete specimen was then tested. The test results (peeling strength after aging at 80°C for 168 h) are shown in Table 1.

[0085] (2-3) The peeling specimen was placed in 60°C hot water and aged for 168 h in the 60°C hot water (i.e., kept warm in 60°C hot water for 168 h). Then, the peel strength between the composite polymer membrane in the peeling specimen and the concrete specimen was tested. The test results (peel strength after aging at 60°C hot water for 168 h) are shown in Table 1.

[0086] In the peel strength test in (2-1) to (2-3) above, the coiled material specimen (peeling specimen) is adhered to the surface of the base layer with reference to GB / T 328.20 standard, and the width of the bonding surface is 50 mm and the length is 100 mm. Then, the peeling test is carried out at a speed of (100±10) mm / min to measure the peel strength.

[0087] Examples 2 to 16, Comparative Example 1: The difference from Example 1 is that the composition of component A and the composition of component B and other conditions are different, see Table 1 and Table 2 for details. Except for the differences shown in Table 1 and Table 2, the other conditions are the same.

[0088] Among them, the only difference between Example 16 and Example 1 is that polyester polyol is added to component A, and polyester polyol is not added to component B. Apart from this, the amount (mass) of isocyanate, the amount (mass) of silane coupling agent, the amount (mass) of the first plasticizer, the amount (mass) of polyester polyol, the amount (mass) of polyether polyol, the amount (mass) of small molecule alcohol, the amount (mass) of pigment, the amount (mass) of second plasticizer, the amount (mass) of antioxidant, the amount (mass) of catalyst, the amount (mass) of water and other conditions are the same as those in Example 1.

[0089] Table 1

[0090]

[0091] Note: The mass proportion of each component in Table 1 refers to the mass ratio of the component to component A.

[0092] Table 2

[0093]

[0094] Note: The mass proportion of each component in Table 2 refers to the mass ratio of the component to component B.

[0095] Table 3

[0096]

[0097] As can be seen from Table 1, compared with Comparative Example 1, Examples 1 to 12 can significantly improve the adhesion of the adhesive, as well as aging resistance such as heat resistance and hydrolysis resistance by adding small molecule alcohol to component B. After the composite polymer coil and the base layer are bonded by the adhesive, the peel strength before aging, the peel strength after aging in an 80°C oven, and the peel strength after aging in hot water at 60°C are significantly improved. This shows that the solvent-free two-component foaming adhesive for the composite polymer coil of the embodiment of the present invention has good bonding strength and aging resistance.

[0098] In addition, during the peeling test, the failure of the backing of the composite polymer coil occurred before the composite polymer coil was peeled off from the base layer (i.e., the bonding failure form was the failure of the backing of the composite polymer coil), indicating that the bonding strength of the adhesive was greater than the strength of the composite polymer coil itself bonded to the base layer, further illustrating that the adhesive of the embodiment of the present invention has good bonding strength and aging resistance.

[0099] In addition, it can be seen from Comparative Example 1, Example 3, Example 1, Example 4, and Examples 6 to 8 that as the amount of small molecule alcohol added in component B increases, the peel strength between the composite polymer coil and the base layer tends to first increase and then decrease. Therefore, by further controlling the mass proportion of small molecule alcohol in component B within an appropriate range, it is beneficial to further improve the adhesion and aging resistance of the adhesive and improve the peel strength between the composite polymer coil and the base layer.

[0100] Furthermore, compared with Example 16, Example 1 adds polyester polyol to component B, which is beneficial to further improve the adhesion and aging resistance of the adhesive.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adhesive, characterized in that: The invention comprises component A and component B, wherein the component A is an isocyanate component, and the component B comprises a polymer polyol, a small molecule alcohol and water.

2. The adhesive according to claim 1, characterized in that: The small molecule alcohol includes one or more diols with 2 to 9 carbon atoms; preferably, the small molecule alcohol includes one or more diols with 4 to 8 carbon atoms; And / or, in the B component, the mass percentage of the small molecule alcohol is 5% to 25%, preferably 5% to 15%; And / or, in the component B, the mass percentage of water is 0.1% to 1.5%.

3. The adhesive according to claim 1, characterized in that: The polymer polyol includes polyether polyol and / or polyester polyol.

4. The adhesive according to claim 3, characterized in that: The hydroxyl value of the polyether polyol is 164-168 mgKOH / g; And / or, the polyether polyol comprises a polyether polyol having a functionality of 3; And / or, in the B component, the mass percentage of the polyether polyol is 15% to 39%; and / or, the polyester polyol has a hydroxyl value of 54 to 58 mgKOH / g; And / or, the polyester polyol comprises a polyester polyol having a functionality of 2; And / or, in the component B, the mass percentage of the polyester polyol is 15% to 39%.

5. The adhesive according to any one of claims 1 to 4, characterized in that: The B component also includes an auxiliary agent, which includes one or more of a pigment, a second plasticizer, an antioxidant, and a catalyst; Preferably, the pigment comprises red iron oxide and / or phthalocyanine green; Preferably, the second plasticizer comprises chlorinated paraffin; Preferably, the catalyst comprises an organometallic catalyst; Preferably, in the B component, the mass percentage of the pigment is 0.2% to 5%; Preferably, in the B component, the mass percentage of the second plasticizer is 5% to 25%; Preferably, in the B component, the mass percentage of the antioxidant is 0.1% to 2%; Preferably, in the B component, the mass percentage of the catalyst is 0.1% to 2%.

6. The adhesive according to any one of claims 1 to 4, characterized in that: The A component includes isocyanate modified by a silane coupling agent; And / or, the A component includes a first plasticizer.

7. The adhesive according to claim 6, characterized in that: The silane coupling agent-modified isocyanate is obtained by modifying isocyanate with a silane coupling agent, wherein the isocyanate includes polymethylene polyphenyl isocyanate, and / or the silane coupling agent includes 3-mercaptopropyl triethoxy silane coupling agent (KH-580) and / or 3-mercaptopropyl trimethoxy silane coupling agent; and / or, the first plasticizer comprises chlorinated paraffin; And / or, in the component A, the mass percentage of the isocyanate modified by the silane coupling agent is 50.1% to 80.9%; And / or, in the component A, the mass percentage of the first plasticizer is 5% to 25%.

8. The adhesive according to any one of claims 1 to 4, characterized in that: The adhesive is a foaming adhesive; And / or, the volume ratio of the component A to the component B is 1:(1-1.2).

9. A method for preparing the adhesive according to any one of claims 1 to 8, characterized in that: Including the preparation process of the A component and the preparation process of the B component; The preparation process of the component A includes: modifying isocyanate with a silane coupling agent to obtain isocyanate modified by the silane coupling agent; mixing a first plasticizer and the isocyanate modified by the silane coupling agent to obtain the component A; The preparation process of the B component includes: uniformly mixing raw materials for forming the B component to obtain the B component; wherein the raw materials for forming the B component include polymer polyols, small molecule alcohols and water.

10. Use of the adhesive according to any one of claims 1 to 8 in bonding a composite polymer coil and a base layer.